2021
DOI: 10.3390/ijerph182312731
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationships among Strategic Experiential Modules, Motivation, Serious Leisure, Satisfaction and Quality of Life in Bicycle Tourism

Abstract: It seems that people’s quality of life can be positively influenced through bicycle tourism. Bicycle tourism can be an effective measure to enhance serious leisure, tourism satisfaction, and quality of life. To verify this empirically, a survey was conducted of bicycle tourists who visited Qinghai Lake in China during an international road bike race. The purpose of the present research is to prove the association between latent variables related to bicycle tourism through statistical analysis. For this, hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The agreement on all seven factors as learning competency, content, language, social content, assessment, format and technical specifications, and intellectual property rights as rated by the experts refer to the compliance to the standards of the department of education on learning resource development. These results are consistent with the student's satisfaction based on the content, format, and style of modules [34]. Modules earning a "passed" decision by the experts on all factors imply the favorable recommendation for approval to use in the basic education for public senior high schools in the region.…”
Section: Validation By Experts' Evaluation Of the Quality Of Drrm Mod...supporting
confidence: 75%
“…The agreement on all seven factors as learning competency, content, language, social content, assessment, format and technical specifications, and intellectual property rights as rated by the experts refer to the compliance to the standards of the department of education on learning resource development. These results are consistent with the student's satisfaction based on the content, format, and style of modules [34]. Modules earning a "passed" decision by the experts on all factors imply the favorable recommendation for approval to use in the basic education for public senior high schools in the region.…”
Section: Validation By Experts' Evaluation Of the Quality Of Drrm Mod...supporting
confidence: 75%
“…Mobility could aid in flourishing the places visited [70], encountering locals along the way, and contributing later to well-being [71]. Eudaimonic experiences could be seen as a form of serious leisure, and the latter is positively associated with cycling tourists' level of satisfaction and quality of life [72]. Cycling could enhance mood and overall feelings of well-being, with an existent positive relation between cycling, self-actualisation, selfefficacy dimensions, and positive mood [73].…”
Section: Eudaimonic Experiencesmentioning
confidence: 99%
“…Structural equation modeling shows that self-esteem partially mediates the relationship between perceived poverty and life satisfaction (Liu Bin et al, 2022). In other quality-of-life studies of sports, serious leisure levels in cycling tourism were found to have a positive impact on satisfaction and quality of life (Rui Guo et al, 2021). In health studies, decreased quality of life (QOL) is associated with shorter survival and is more pronounced in patients with end-stage renal disease (ESRD).…”
Section: Relevant Literature and Research Reviewmentioning
confidence: 99%